Changes in oxidative markers, endogenous antioxidants and activity of the enzyme acetylcholinesterase in farmers exposed to agricultural pesticides - a pilot study - Murussi,Camila (2014)
Agricultural practices are directly related to the use of pesticides, which indiscriminately and without due care may contribute to the occurrence of numerous intoxications. Several studies have demonstrated the relationship of certain pesticides and the occurrence of oxidative stress and therefore, in recent years have developed methods of analysis of several biomarkers of cellular damage that can be measured and quantified. In this context, the objective of this study was to evaluate the possible changes in biochemical markers: glutamic aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, urea, total protein, and oxidative markers such as lipid peroxidation, damage to proteins and the activity of the enzymes acetylcholinesterase (AChE) and catalase (CAT) in farmers exposed to different pesticides for at least five years from Ibirubá - RS city. With the exception of AST and ALT, the results showed a significant difference between the mean total protein, urea and creatinine in the control group, showing that no changes in liver or kidney function of rural workers. In the oxidative parameters, there was a decrease in AChE activity and CAT in the control group; there were an increase in protein carbonyl and a decreased on TBARS compared to control group. Therefore, the results demonstrated a change in oxidative status of rural workers compared with the control group, mainly by possible inhibition of AChE activity and the occurrence of oxidative stress without showing changes in biochemical parameters.